Asthma and youth soccer: an investigation into the level of asthma awareness and training among youth soccer coaches - Sadasivan C; Cave A (Dove Medical Press, 2019)
Chandu Sadasivan, Andrew Cave Department of Family Medicine, University of Alberta, Edmonton, AB, Canada Purpose: Asthma is the most common chronic disease among children. Exercise-induced bronchoconstriction which is common in asthmatic patients also occurs in individuals with no prior asthma diagnosis. Despite this and the fact that soccer is a high ventilation sport, there are no validated asthma management protocols in place for soccer coaches. This study aims to address 1) soccer coaches’ current knowledge on asthma, 2) whether there is a need for asthma-related training, and 3) any barriers to administration of such training.Patients and methods: A total of 2,300 volunteer youth soccer coaches from the Edmonton Minor Soccer Association (EMSA) were invited to participate in completing a 22-question online survey. The survey was open for 1 month from June 8, 2018, to July 8, 2018.Results: There was a response rate of 22% (513 of 2,300). Respondents were on average, inexperienced coaches, coached younger age groups, and approximately one-third of respondents had personal experience with asthma (either themselves or their child had asthma). 93% of respondents had not received any asthma-related training at any coaching level, whether it be from EMSA or the Alberta Soccer Association. Coaches had strong knowledge on how to treat asthma attacks, but mixed levels of knowledge on asthma attack prevention. Experienced coaches were better at identifying the number of players with asthma on their team and the number of asthma-related incidents they had encountered as coaches. Coaches demonstrated a receptive attitude toward receiving asthma-related training, with 91% of respondents saying training would be beneficial and 69% of respondents saying training should be mandatory.Conclusion: The results of this study indicate that soccer coaches have limited knowledge regarding asthma management, acknowledge a need for asthma-related training, and are willing to participate in and could benefit from educational interventions as it pertains to their roles as coaches. Keywords: coaching, exercise-induced bronchoconstriction, management, protocol